Organizational recognition of the contributive uniqueness: construction of an instrument for its assessment - Leitão, Carla Cabo (2011)
People, by their unique and changeable character, are presently a valuable and active organizational factor that can make a difference in an organization. The present study aimed to create an instrument that could provide additional information about organizational recognition of employees’ contributive uniqueness. After consulting the literature and analyzing interviews to 10 workers, the first version of the subsequent set of items was elaborated and applied to 384 employees. The KMO and Bartlett’s test indicated that it was possible to proceed to the EFA. In the final solution, obtained with varimax rotation, the questionnaire had 20 items composed by 4 factors with Cronbach alpha’s values above .70. We further conducted some differential studies with demographic variables. The results showed significant differences between the questionnaire’s dimensions and the studied demographic variables and reinforced the importance of recognizing one’s contributive uniqueness as an important asset for organizational development and increased value; Resumo: Pelo seu carácter único e modificável, as pessoas são presentemente um factor valioso e activo que pode fazer a diferença numa organização. O presente estudo teve como objectivo criar um instrumento que forneça informação adicional acerca do reconhecimento organizacional da singularidade contributiva. Após consultada a literatura e analisadas 10 entrevistas a trabalhadores, a primeira versão dos subsequentes itens foi elaborada e aplicada a 384 trabalhadores. O KMO e teste de Bartlett indicaram que era possível proceder à AFE. Na solução final, obtida com rotação varimax, o questionário teve 20 itens composto por 4 factores com valores de alfa de Cronbach acima de .70. Posteriormente foram conduzidos estudos diferenciais com variáveis demográficas. Os resultados demonstram diferenças significativas entre as dimensões do questionário e as variáveis demográficas estudadas reforçando assim, a importância de reconhecer a singularidade contributiva como um importante contributo para o desenvolvimento organizacional e para a incrementação do seu valor.